"The Horror" of Structural Racism: Helping Students Take a Critical Stance Using Classic Literature. (3rd April 2017) - McCardle, Todd
Abstract : The goal of this piece is to provide educators with the knowledge and practical application needed to build critical literacy within their students using a traditional text that might not be considered multicultural. This essay challenges the idea that "outdated" literary works have no place in today's multicultural classroom, as it connects critical literacy concepts to classic works and explores how such concepts are inherent in our society based on the ideas presented in the literature. Using Heart of Darkness, this work connects structural racism to Conrad's novella and explores how students can examine how structural racism is inherent in our society.